Health benefits of xylitol consumption - a literature review - Brzoza, Martyna; Stawińska-Dudek, Julia; Mikołajczyk, Piotr; Buras, Barbara; Orzeł, Milena; Orzeł, Bartłomiej; Bielecka, Aleksandra; Dubniański, Bartosz; Stawińska, Kornelia (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Throughout the years xylitol has become a commonly used sugar substitute. Presenting similar level of sweetness to sucrose, it serves as a much healthier alternative. The aim of this article is to expand knowledge about the beneficial impact of xylitol on human health mainly focusing on aspects regarding oral health. Materials and methods: A thorough analysis of scientific databases such as PubMed and Google Scholar has been undertaken using the key words chosen based on their relevance to the matter in subject. Studies since the year 2017 have been analyzed in order to obtain the most up to date information. The state of knowledge: Xylitol, being the sweetest of all polyols, has been prevalently used as a sugar substitute due to its various favorable effects on both oral and general health. It may be incorporated into daily oral care regimen as a preventive measure counteracting caries development both in adults and in children. According to the investigated studies, it also acts as a prebiotic, presents low caloric value as well as low glycemic and insulinemic indices. Conclusions: Xylitol is characterized by its facile availability in various forms such as for example chewing gums, pastilles, toothpastes, wipes and mouth rinses. It is derived either from natural, mainly plant based sources, or it may also be extracted synthetically. Due to those reasons and its favorable properties, it may serve as a prevalent sugar substitute. Used in appropriate doses it is safe regardless of age and presents multiple advantageous effects on various aspects of human health.